Harbor Sedimentation Management Using Numerical Modeling and Exploratory Data Analysis - Mohamed T. Elnabwy; Emad Elbeltagi; Mahmoud M. El Banna; Abdullah H. Alshahri; Jong Wan Hu; Byoung Gil Choi; Yong Hee Kwon; Mosbeh R. Kaloop (Advances in Civil Engineering)
Sedimentation in the harbors’ basins is an environmental phenomenon that frequently disrupts safe shipping and necessitates costly dredging operations. The layout of harbors and the permeability of protective structures such as breakwaters influence sediment transport within harbor basins. Thus, through a multistep framework, this study investigates the sedimentation management issues for the Egyptian proposed Ezbet Elborg fishing harbor based on field measurements and a numerical morphodynamic coastal modeling system (CMS). First, field measurements were analyzed and evaluated for acquiring a full grasp of the research area’s bathymetry and hydrodynamics. Second, a two-dimensional (2D) numerical simulation CMS model was set up and calibrated against field measurements wherein the developed CMS model highly correlated with actual measurements by 97%. CMS results demonstrate that the predominant NNW wave with the formed longshore current on both the harbor’s sides affects sediment accumulation within the harbor’s basin. Third, 100 simulations for the proposed harbor including different structural modulation scenarios affecting the sedimentation issue were investigated via the calibrated CMS model. Finally, an exploratory data analysis (EDA) is performed via correlation matrix and ANOVA test for the CMS’s scenarios’ results to gain an in-depth view of the relation between the harbors’ layout and the structural characteristics with the sedimentation volumes. Results showed that breakwaters’ orientation affects sediment accumulation more than its length. Also, breakwater permeability and basin width are significantly affecting sediment accumulation. Ultimately, the current study makes a substantial contribution to integrated coastal structure management (ICSM) by helping coastal stakeholders to mitigate the negative impacts of the harbors’ sediment deposition aiming at sustaining both environmental and economic aspects.